2014
DOI: 10.1016/j.ophtha.2013.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Use of Health Care Claims Data to Study Patients with Ophthalmologic Conditions

Abstract: Objective To describe what information is or is not included in health care claims data, provide an overview of the main advantages and limitations of performing analyses using health care claims data, and offer general guidance on how to report and interpret findings of ophthalmology-related claims data analyses. Design Systematic review. Participants Not applicable. Methods A literature review and synthesis of methods for claims-based data analyses. Main Outcome Measures Not applicable. Results Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
82
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 38 publications
0
82
0
Order By: Relevance
“…As such, the findings may have more generalizability relative to single center studies or those from academic centers that may be a biased sample of those with more severe disease. 44 In addition, claims data does not rely on patient self-report of medical conditions such as KCN. Others have demonstrated patient self-report is less reliable compared with diagnoses made by medical professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the findings may have more generalizability relative to single center studies or those from academic centers that may be a biased sample of those with more severe disease. 44 In addition, claims data does not rely on patient self-report of medical conditions such as KCN. Others have demonstrated patient self-report is less reliable compared with diagnoses made by medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…First, without access to clinical records, we cannot confirm the presence of KCN among those identified as cases or absence of disease in controls. 44 That said, a study by Center for Medicare and Medicaid Services found the specialty of ophthalmology has one of the lowest rates of improper coding of ocular diagnoses. 46 Moreover, to help ensure that those who had been coded with KCN did indeed have the disease we required a confirmatory diagnosis on a separate visit.…”
Section: Discussionmentioning
confidence: 99%
“…36 Claims data lack the detailed clinical information needed to determine the appropriateness of testing that was or was not performed. Likewise, we lacked information on eye care providers’ access to testing equipment to perform these tests or the cost of such equipment, which may have affected utilization.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies using secondary data, including administrative databases such as MarketScan are not without merit. Administrative databases, including MarketScan data have been used for numerous research studies published in peer-reviewed journals [34,35]. Advantages of such databases include having multiple years of data for diverse populations that include demographic, health care related, and other information [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Administrative databases, including MarketScan data have been used for numerous research studies published in peer-reviewed journals [34,35]. Advantages of such databases include having multiple years of data for diverse populations that include demographic, health care related, and other information [34,35]. A number of reports on ICD-9-CM -coded information for VTE diagnoses in selected inpatient data sources have suggested positive predictive values of approximately 65%–95% for several of the codes used in our study to identify VTE diagnoses when present in inpatient hospital discharges [31,32].…”
Section: Discussionmentioning
confidence: 99%